Adsorption study using optimised 3D organised mesoporous silica coated with Fe and Al oxides for specific As(III) and As(V) removal from contaminated synthetic groundwater - Glocheux, Yoann; Albadarin, Ahmad B.; Galán, José; Oyedoh, Eghe; Mangwandi, Chirangano; Gérente, Claire; Allen, Stephen J.; Walker, Gavin M. (My University, 2025)
This work presents the possibility of optimising 3D organised mesoporous silica (OMS) coated with both iron and aluminium oxides for the optimal removal of As(III) and As(V) from synthetic contaminated water. The materials developed were fully characterised and were tested for removing arsenic in batch experiments. The effect of total Al to Fe oxides coating on the selective removal of As(III) and As(V) was studied. It was shown that 8% metal coating was the optimal configuration for the coated OMS materials in removing arsenic. The effect of arsenic initial concentration and pH, kinetics and diffusion mechanisms was studied, modelled and discussed. It was shown that the advantage of an organised material over an un-structured sorbent was very limited in terms of kinetic and diffusion under the experimental conditions. It was shown that physisorption was the main adsorption process involved in As removal by the coated OMS. Maximum adsorption capacity of 55 mg As(V) g¿1 was noticed at pH 5 for material coated with 8% Al oxides while 35 mg As(V) g¿1 was removed at pH 4 for equivalent material coated with Fe oxides.